Clinical study of reoperation for acute type A aortic dissection - Feng, Yi; Ma, Xian-Tao; Zhang, Xiao-Xue; Wajeehullahi, Akilu; Chen, Zi-Jun; Li, Shi-Liang; Cheng, Cai (Frontiers in Cardiovascular Medicine, 2024)
Objective The initial operation for type A aortic dissection has limitations, and there may be a need for reoperation in cases such as giant pseudoaneurysm formation and reduced blood supply to the distal vessels. In this study, we collected case data of patients who underwent cardiac major vascular surgery at our hospital to analyze the effectiveness of reoperation treatment options for type A aortic dissection and to summarize our treatment experience. Method Between June 2018 and December 2022, 62 patients with type A aortic dissection (TAAD) underwent reoperation after previous surgical treatment. Of these, 49 patients (45 males) underwent endovascular aortic repair (EVAR) with a mean age of (49.69 ± 10.21) years (30–75 years), and 13 patients (11 males) underwent thoracoabdominal aortic replacement (TAAR) with a mean age of (41.00 ± 11.18) years (23–66 years). In this study, we retrospectively analyzed the recorded data of 62 patients. In addition, we summarized and analyzed their Computed Tomographic Angiography (CTA) results and perioperative complications. Outcome In the EVAR group, 47 patients (95.92%) were successfully implanted with overlapping stents, and 2 patients died in the perioperative period. Postoperative complications included cerebral infarction (4.08%), acute renal insufficiency (30.61%), pulmonary insufficiency and need for ventilator (6.12%), poor wound healing (2.04%), postoperative reoperation (16.33%), and lower limb ischemia (2.04%). In the TAAR group, 12 patients (92.31%) were successfully revascularized and 1 patient died in the perioperative period. Postoperative complications included cerebral infarction (7.69%), acute kidney injury (46.15%), pulmonary insufficiency and need for ventilator (15.38%), poor wound healing (30.77%) and postoperative reoperation (15.38%). Conclusion According to the results of the study, compared with TAAR, EVAR was less invasive, faster recovery, and offered a better choice for some high-risk and high-age patients with comorbid underlying diseases. However, the rate of revascularization was higher after EVAR than TAAR due to vascular lesions. Compared with the use of ascending aortic replacement + hemi-aortic arch replacement for acute type A aortic dissection in many countries and regions, the use of ascending aortic replacement + aortic arch replacement + elephant trunk stent is more traumatic in China, but facilitates reoperation. For young patients, the choice of treatment should be individualized combining vascular lesions and long-term quality of life.